The Effect of Good Corporate Governance, Corporate Social Responsibility, and Profitability on Firm Value in Energy Sector Companies Listed on the Indonesia Stock Exchange - Parso Parso (Sean Institute, 2026)
This study examines the influence of Good Corporate Governance, Corporate Social Responsibility, and profitability on firm value in energy sector companies listed on the Indonesia Stock Exchange. The research adopts a quantitative approach using secondary data derived from annual financial statements and sustainability reports. The analysis is conducted using panel data regression to evaluate both partial and simultaneous effects of the independent variables on firm value. The findings reveal that profitability has a positive and significant influence on firm value, indicating that financial performance remains the primary consideration for investors in assessing company prospects. In contrast, Good Corporate Governance shows a positive but not significant effect, suggesting that governance mechanisms are not consistently perceived as value drivers by the market. Similarly, Corporate Social Responsibility does not demonstrate a significant impact, implying that its benefits may be more long-term and not directly reflected in short-term market valuation. However, the simultaneous results indicate that all variables collectively influence firm value, highlighting the importance of integrating financial and non-financial factors in corporate performance. This study contributes to the literature by providing empirical evidence from the energy sector and offers insights for companies to balance profitability, governance practices, and social responsibility in enhancing firm value.